Rancangan Sistem Otomatis Start dan Monitoring Air Handling Unit Terminal 2 Bandar Udara Internasional Soekarno - Hatta - Muhammad Fahri; KGS ISMAIL; Oka Fatra (Politeknik Penerbangan Indonesia Curug, 2021)
Terminal 2 of Soekarno-Hatta has 97 Air Handling Units (AHU) which are used to condition room temperature. When there is a disconnection or interruption to the power supply, all AHUs must be turned on by visiting the unit. The automatic start and monitoring design using PLC supported by a visual basic program is expected to help the operational effectiveness of AHU. This design has a connection between PLC and PC using wifi, where the monitoring function when operating the AHU unit will be displayed on the monitor and the control function of the AHU unit operation can be done remotely, and is equipped with an automatic start system, namely, when the power supply is cut off and reconnected, AHU can operate immediately without manually activating it.